Training on the Production of Cassava Plant Waste Silage as Goat Feed in Penyasawan Village, Kampar Regency - Maulina Novita; Dedi Ramdani; Rahmat Hidayat; Vebrita Sari (Journal of Social and Community Service, 2026)
Kampar Regency has great potential in the goat farming sector; however, farmers frequently encounter constraints regarding the limited availability of quality feed, particularly during the dry season. This Community Service Program aims to enhance the knowledge and skills of farmers in Penyasawan Village through training on alternative feed processing technology in the form of cassava leaf waste silage. The implementation methods encompass partner problem identification, socialization, theoretical counseling, and practical demonstrations of anaerobic silage-making over a period of 21 days. The activity results demonstrated an 80,7% increase in participant understanding, which is reflected by the rise in the average post-test score (82.4) compared to the pre-test (45.6). The resulting silage met good quality standards, characterized by a fresh acidic aroma, a non-slimy texture, and a pH range of 3.8 to 4.2. Economically, the adoption of this technology has the potential to save feed costs by IDR 450,000 to IDR 600,000 per month for 10 goats, while simultaneously supporting a sustainable farming system and a village-level circular economy.